(untitled) (Actual Problems of Psychology in Educational Institutions, 2023)
The article reveals the peculiarities of using technologies for interactive learning of students in the organization of project activities. The role and place of the project method in the conditions of distance education is analyzed. Examples of interactive technologies from the positive experience of their implementation in project activities are offered. The psychological content of the use of interactive technologies in the teacher’s project activity in the lesson is revealed. Emphasis is placed on the psychological features of the use of interactive learning technologies in the format of subject-subject interaction between teachers and students in a distance learning format. The pros and cons of using interactive learning technologies in organizing project activities are outlined.